2016
DOI: 10.1055/s-0036-1584165
|View full text |Cite
|
Sign up to set email alerts
|

Breast Augmentation by Water-Jet Assisted Autologous Fat Grafting: A Report of 300 Operations

Abstract: Autologous fat transfer for breast augmentation is gaining more acceptance as an alternative to implants because only autologous filling materials are used and because undesirable fat can be removed from other regions as an additional benefit. The advantages of breast augmentation with autologous fat include the lack of reactive inflammation, foreign body reaction, and scars as well as the natural-appearing result with more volume, an improved contour, a fuller cleavage, and natural consistency.The competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(63 reference statements)
0
8
0
1
Order By: Relevance
“…Im weiteren kann eine Schädi-gung des Gewebes und insbesondere der Lymphbahnen durch "aggressivere" mechanische Absaugverfahren nicht ausgeschlossen werden: Vibrationskanülen, Ultraschallgeräte oder laserassistierte Lipolyseverfahren traumatisieren das Gewebe mehr als der sanfte Wasserstrahl, welcher, der Kanülenspitze vorausgehend, einen natürlichen Weg durch das Gewebe bahnt und dadurch Gefäße, Lymphbahnen und Nerven nicht verletzt [1]. Aus diesen Gründen hat sich die WAL auch als erfolgreiche Methode zur schonenden Gewinnung intakter Fettpartikel beim autologen Fetttransfer etabliert [10,18].…”
Section: Konservative Therapieunclassified
“…Im weiteren kann eine Schädi-gung des Gewebes und insbesondere der Lymphbahnen durch "aggressivere" mechanische Absaugverfahren nicht ausgeschlossen werden: Vibrationskanülen, Ultraschallgeräte oder laserassistierte Lipolyseverfahren traumatisieren das Gewebe mehr als der sanfte Wasserstrahl, welcher, der Kanülenspitze vorausgehend, einen natürlichen Weg durch das Gewebe bahnt und dadurch Gefäße, Lymphbahnen und Nerven nicht verletzt [1]. Aus diesen Gründen hat sich die WAL auch als erfolgreiche Methode zur schonenden Gewinnung intakter Fettpartikel beim autologen Fetttransfer etabliert [10,18].…”
Section: Konservative Therapieunclassified
“…[6][7][8][9][10][11][12][13][14][16][17][18] The included studies' characteristics are shown in Table 1. There were 15 prospective studies, 8,[10][11][12][13][14]18,[22][23][24]28,30,31,35,39 17 retrospective studies, 6,7,9,16,17,20,21,[25][26][27][32][33][34][35][36][37]40 and three randomized controlled trials. 29,38,41,43 A total of 3757 women were included, and the mean age was 40.5 years (range, 17 to 78 years).…”
Section: Resultsmentioning
confidence: 99%
“…Complications were reported in 20 studies 6,7,10,12,14,18,[20][21][22][23][24][25]27,29,30,33,[36][37][38]42 ; the overall complication rate was 27.8% (Table 3). The most common benign findings included fat necrosis, indurations, and oil cysts.…”
Section: Graft Complicationsmentioning
confidence: 99%
“…Current liposuction methods include the water-jet–assisted liposuction, the conventional liposuction, and the ultrasound-guided liposuction 13,14 . Water-jet–assisted liposuction is a favorable procedure for lipoaspirates collection using a mild liquid spray 15,16 . It can reduce mechanical damage to fat tissue.…”
mentioning
confidence: 99%
“…The water-jet–assisted liposuction could obtain more viable adipocytes and achieve better fat survival 16 . Moreover, it has significant advantages in reducing intraoperative pain and swelling, improving contouring, and postoperative recovery compared with the conventional liposuction 15,18 …”
mentioning
confidence: 99%